CROWDFUNDING AND ISLAMIC SECURITIES: THE ROLE OF FINANCIAL LITERACY - Rifaldi Majid; Rizky Aditya Nugraha (Journal of Islamic Monetary Economics and Finance, 2022)
This study investigates the effect of Islamic Financial Literacy (IFL) on the intention of prospective Muslim investors to invest through the Islamic securities crowdfunding FinTech (I-SCF FinTech) platform. Using data gathered from 100 respondents and employing the Partial Least Square – Structural Equation Modeling, we find IFL to have a significant effect on behavioral intention. The results of this study should benefit those involved in the I-SCF FinTech. Further, they point to the need to strengthen product and contract literacy and the importance of supervision and implementation of contracts that are in line with sharia principles through synergy between the Financial Service Authority (OJK) and the crowdfunding FinTech associations as well as relevant stakeholders.